(untitled) (Palíndromo, 2020)
This article seeks to reflect on a set of images that have as common the grotesque body. Narratives about the anus and eschatological narratives are explored. From the images analyzed, I discuss questions about the relationship between image and writing in two aspects: the first comprises the game between writing and image present in an anonymous diptych of the 16th century, where writing seeks to alert the viewer not to open the diptych; The second question analyzed concerns the presence of proverbs that translate into images in the works of Pieter Bruegel and Hendrick Avercamp.